2017
DOI: 10.1108/et-01-2017-0002
|View full text |Cite
|
Sign up to set email alerts
|

Examining US college students’ career information sources across three decades

Abstract: Purpose The purpose of this paper is to examine the career information sources used by university students and identify whether the use of the various sources differs across three generational cohorts. Design/methodology/approach A survey was administered to 322 students majoring in food marketing and related fields at 12 US universities. The results were compared to prior survey results from 1995 to 2004. Findings Students continue to use many of the same sources for career information, but use them more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 61 publications
1
15
0
Order By: Relevance
“…It is imperative for employers to know whether values have changed across recent cohorts, so that they can continue to attract and retain the future workforce. Also, given that students are increasingly relying on career counselors for career information (Zondag & Brink, 2017), it is important for employment counselors to understand the values of college graduates, so that they can manage student expectations and facilitate a match between students and employers. The popular press frequently opines about generational differences, yet we are not aware of any prior empirical research that compares U.S. millennial college students’ job attribute preferences across generations.…”
mentioning
confidence: 99%
“…It is imperative for employers to know whether values have changed across recent cohorts, so that they can continue to attract and retain the future workforce. Also, given that students are increasingly relying on career counselors for career information (Zondag & Brink, 2017), it is important for employment counselors to understand the values of college graduates, so that they can manage student expectations and facilitate a match between students and employers. The popular press frequently opines about generational differences, yet we are not aware of any prior empirical research that compares U.S. millennial college students’ job attribute preferences across generations.…”
mentioning
confidence: 99%
“…web-based resources, peer networks). In a longitudinal study that tracked the quality and frequency of career information sources of more than 1,000 US college students with food marketing-related majors, Zondag and Brink (2017) found that college professors and courses were rated as the most useful sources of career information, followed by career fairs, jobs or internships, and family members. The authors also found that while CSCs and career counselors were not as highly rated, they were widely viewed by students as an important source of career information.…”
Section: Background: Developmental Theories and Career Information-seeking Behaviorsmentioning
confidence: 99%
“…Despite increasing interest in and scrutiny of CSCs, however, limited empirical research has examined students’ own experiences with and perspectives about the types of information provided by CSCs. A promising line of inquiry has examined students’ satisfaction with CSCs in Canada (Usher and Kwong, 2014) and the USA (Gallup-Purdue Index Report, 2016) and two survey-based studies of students’ utilization of various career information resources shed important light on this issue (Pesch et al , 2018; Zondag and Brink, 2017). Yet to our knowledge no studies have examined, at a more fine-grained level than is available through survey research, precisely how students experience and interpret the informational resources provided by CSCs or other units on a college or university campus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because sense of fit is critical to retention of people in engineering careers, exploring alternative methods for students to communicate about fit and skill development could be important, and the faculty and other career professionals that comprise CDMS could be appropriate touch points for students. Third, although students, industry and academia are all stakeholders they have different costs, benefits and interests regarding internships (Maertz et al , 2014) and research on college students has shown that faculty remain an important source of career information for students over time and engagement with career centers and counselors is growing (essentially CDMS as defined herein) (Zondag and Brink, 2017). For all of these reasons, the academic stakeholder perspective best suits the need to understand the current state of who is engaging with students and how this engagement occurs, regarding internship experiences.…”
Section: Introductionmentioning
confidence: 99%